Can Stereotactic Body Radiation Therapy Be a Viable and Efficient Therapeutic Option for Unresectable Locally Advanced Pancreatic Adenocarcinoma? Results of a Phase 2 Study. (June 2017) - Comito, Tiziana; Cozzi, L.; Clerici, E.; Franzese, C.; Tozzi, A.; Iftode, C.; Navarria, P.; D'Agostino, G.; Rimassa, L.; Carnaghi, C.; Personeni, N.; Tronconi, M. C.; et al.
Purpose: To assess the efficacy of stereotactic body radiotherapy in patients with unresectable locally advanced pancreatic cancer. Materials and Methods: All patients received a prescription dose of 45 Gy in 6 fractions. Primary end point was freedom from local progression. Secondary end points were overall survival, progression-free survival, and toxicity. Actuarial survival analysis and univariate or multivariate analysis were investigated. Results: Forty-five patients were enrolled in a phase 2 trial. Median follow-up was 13.5 months. Freedom from local progression was 90% at 2 years. On univariate ( P < .03) and multivariate analyses ( P < .001), lesion size was statistically significant for freedom from local progression. Median progression-free survival and overall survival were 8 and 13 months, respectively. On multivariate analysis, tumor size ( P < .001) and freedom from local progression ( P < .002) were significantly correlated with overall survival. Thirty-two (71%) patients with locally advanced pancreatic cancer received chemotherapy before stereotactic body radiotherapy. Median overall survival from diagnosis was 19 months. Multivariate analysis showed that freedom from local progression ( P < .035), tumor diameter ( P < .002), and computed tomography before stereotactic body radiotherapy ( P < .001) were significantly correlated with overall survival from diagnosis. Conclusion: Stereotactic body radiotherapy is a safe and effective treatment for patients with locally advanced pancreatic cancer with no G3 toxicity or greater and could be a promising therapeutic option in multimodality treatment regimen.